Characteristics and Outcomes of MI Patients with and without Chest Pain: A Cohort Study - Coventry, L.; Bremner, A.; Williams, Teresa; Celenza, A.; Jacobs, I.; Finn, Judith (Elsevier Ltd, 2015)
Introduction: There are conflicting data on patient characteristics and outcomes of myocardial infarction (MI) patients presenting with and without the symptom of chest pain. Objectives: Compare the characteristics and survival of patients stratified by the symptom chest pain. Methods: This retrospective cohort study identified patients with an emergency department discharge diagnosis of MI, who arrived by ambulance at a teaching hospital in Perth, Western Australia, between January 2008 to October 2009. The cohort was linked to hospital data and the state-based death register; clinical data were extracted by medical record review. Patient characteristics were compared using logistic regression models and survival analysis using Kaplan-Meier curves and Cox regression models. Results: Of 382 patients, 26% presented without chest pain. The odds of presenting without chest pain were increased if aged 80+ (OR 7.54; 95%CI 2.81-20.3) and aged 70-79 years (OR 4.33; 95% CI 1.50-12.5), and female (OR 1.67; 95%CI 0.99-2.82). The adjusted hazard (median follow-up time 2.2 years) of presenting without chest pain was not significantly associated with survival (HR 1.03; 95%CI 0.71-1.48). Conclusion: Characteristics differed between patients with and without chest pain. However, the symptom of chest pain was not associated with survival.